Assessment of the Possible Role of FOXP3 Gene (rs3761548) Polymorphism in Psoriasis Vulgaris Susceptibility and Pathogenesis: Egyptian Study - Magdy Abdelmageed Elsohafy; Ashraf Antar Elghzaly; Hebatallah Mansour Abdelsalam; Mohammad A Gaballah (Wolters Kluwer Medknow Publications, 2019)
Background: Psoriasis is an autoimmune-related chronic inflammatory skin disorder. Psoriasis vulgaris (PV) is the most common form of psoriasis. T regulatory cells (Tregs) are typically considered inhibitors of autoimmune responses. FOXP3 is a master control transcription factor for development and function of Tregs. FOXP3 gene polymorphism changes FOXP3 protein function and quantity leading to Tregs dysfunction that subsequently may be related to PV pathogenesis. Objective: The objective of the present study was to evaluate the possible role of FOXP3 gene (rs3761548) polymorphism in PV pathogenesis. Materials and Methods: One hundred sixty subjects were included in the present study (80 PV patients and 80 well-matched healthy controls). All participants were evaluated by detailed history, general examination, dermatological examination, and psoriasis area and severity index (PASI) score. The detection of FOXP3 gene (rs3761548) polymorphism in patients and controls by PCR-restriction fragment length polymorphism technique was done. Results: There was statistically significant increase in CC genotype and C allele in patients compared to controls, whereas there were non-significant differences in AA and AC genotypes. However, there were non-significant associations between genotype distribution and each of age, sex, family history, PASI score, hair affection, nail affection, hypertension, diabetes mellitus, and body mass index. Conclusion: FOXP3 gene (rs3761548) polymorphism may increase susceptibility of PV and share in its pathogenesis as it leads to changes in FOXP3 protein function and quantity that subsequently affect T-regs functions. Further investigations for the role of other FOXP3 genes polymorphisms in psoriasis pathogenesis and their effects on the treatment response in psoriasis patients are strongly recommended.